Process evaluation of the community-based newborn care program implementation in Geze Gofa district, south Ethiopia: a case study evaluation design - Tsegaye Gebremedhin; Dawit Wolde Daka; Yibeltal Kiflie Alemayehu; Kiddus Yitbarek; Ayal Debie (BMC, 2019)
Abstract Background The Community-Based Newborn Care (CBNC) program is a comprehensive strategy designed to improve the health of newborns during pregnancy, childbirth, and the postnatal period through health extension workers at community levels, although the implementation has not been evaluated yet. Therefore, this study aimed to evaluate the process of the CBNC program implementation in Geze Gofa district, south Ethiopia. Methods A case study evaluation design with a mixed method was employed from May 1 to 31, 2017. A total of 321 mothers who gave birth from September 01, 2016 to February 29, 2017, were interviewed. Similarly, 27 direct observations, six-month document reviews, and 14 key informant interviews were conducted. The quantitative data were entered into Epi-Data version 3.1 and exported to SPSS version 20 for analysis. In the multivariable logistic regression analysis, variables with < 0.05 p-values and Adjusted Odds Ratio (AOR) with 95% Confidence Interval (CI) were used to declare factors associated with maternal satisfaction. The qualitative data were transcribed, translated, coded, and analyzed using thematic analysis. The overall process of program implementation was measured based on pre-determined judgmental criteria. Results The overall level of the implementation process of the CBNC program was 72.7%, to which maternal satisfaction, availability of resources, and healthcare providers' compliance with the national guideline contributed 75.0, 81.0, and 68.0%, respectively. Essential drugs and medical equipment, like vitamin K, chlorohexidine ointment, neonatal resuscitation bags, and masks used in the program were out of stock. Very severe diseases were not treated according to the national guidelines, and the identification of neonatal sepsis cases was poor. Trading occupation (AOR: 0.16, 95% CI: 0.03-0.97) and low wealth status (AOR: 3.11, 95% CI: 1.16-8.36) were factors associated with maternal satisfaction. Conclusion The process of CBNC program implementation was relatively good, although the compliance of healthcare providers with the national guideline and maternal satisfaction with the services was low. Some essential drugs and medical equipment were out of stock. Merchant and low wealth status affected maternal satisfaction. Therefore, healthcare offices should provide crucial medicines and equipment for better program implementation and improve the wealth status of mothers to enhance maternal satisfaction.